2022
DOI: 10.21203/rs.3.rs-1547705/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Plasma Interleukin 6 Levels Predict Long-term Mortality in Aneurysmal Subarachnoid

Abstract: OBJECTIVE: Interleukin 6 (IL-6) is an inflammatory cytokine released into the periphery after stroke, involved in the prognosis of aneurysmal subarachnoid hemorrhage (aSAH). We aimed to explore the relationship between serum IL-6 with long-term mortality after aSAH.METHODS: We retrospectively reviewed the medical records of 18824 SAH patients for collection of serum IL-6 levels during hospitalization from a large, single-center aSAH database of Sichuan University West China Hospital. Patient deaths were determ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
0
0
Order By: Relevance
“…In vitro studies have demonstrated that MS can interfere with the nuclear translocation of NF-κB p65 subunit, thereby limiting its transcriptional activity [9]. This mechanism seems to be critical in curbing the production of pro-inflammatory cytokines such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) [10], which are known to be associated with poor prognosis in SAH patients [11,12]. For instance, a retrospective analysis published in 2022 suggested that serum IL-6 peak was independently associated with long-term mortality in a multivariate model evaluating aneurysmal SAH patients [12].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…In vitro studies have demonstrated that MS can interfere with the nuclear translocation of NF-κB p65 subunit, thereby limiting its transcriptional activity [9]. This mechanism seems to be critical in curbing the production of pro-inflammatory cytokines such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) [10], which are known to be associated with poor prognosis in SAH patients [11,12]. For instance, a retrospective analysis published in 2022 suggested that serum IL-6 peak was independently associated with long-term mortality in a multivariate model evaluating aneurysmal SAH patients [12].…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%
“…This mechanism seems to be critical in curbing the production of pro-inflammatory cytokines such as interleukin-1β (IL-1β), interleukin-6 (IL-6), and tumor necrosis factor-alpha (TNF-α) [10], which are known to be associated with poor prognosis in SAH patients [11,12]. For instance, a retrospective analysis published in 2022 suggested that serum IL-6 peak was independently associated with long-term mortality in a multivariate model evaluating aneurysmal SAH patients [12]. Also, recently, clinical studies have shown a significant reduction in the serum levels of cytokines following the administration of MS [13], indicating a systemic anti-inflammatory action that could be beneficial.…”
Section: Anti-inflammatory Activitymentioning
confidence: 99%